Conformers, infrared spectrum, UV-induced photochemistry, and near-IR-induced generation of two rare conformers of matrix-isolated phenylglycine - Borba, Ana (2014)
The conformational space of α-phenylglycine (PG) have been investigated theoretically at both the DFT/B3LYP/6-311++G(d,p) and MP2/6-311++G(d,p) levels of approximation. Seventeen different minima were found on the investigated potential energy surfaces, which are characterized by different dominant intramolecular interactions: type I conformers are stabilized by hydrogen bonds of the type N-H⋯O=C, type II by a strong O-H⋯N hydrogen bond, type III by weak N-H⋯O-H hydrogen bonds, and type IV by a C=O⋯H-C contact. The calculations indicate also that entropic effects are relevant in determining the equilibrium populations of the conformers of PG in the gas phase, in particular in the case of conformers of type II, where the strong intramolecular O-H⋯N hydrogen bond considerably diminishes entropy by reducing the conformational mobility of the molecule. In consonance with the relative energies of the conformers and barriers for conformational interconversion, only 3 conformers of PG were observed for the compound isolated in cryogenic Ar, Xe, and N2 matrices: the conformational ground state (ICa), and forms ICc and IITa. All other significantly populated conformers existing in the gas phase prior to deposition convert either to conformer ICa or to conformer ICc during matrix deposition. The experimental observation of ICc had never been achieved hitherto. Narrowband near-IR irradiation of the first overtone of νOH vibrational mode of ICa and ICc in nitrogen matrices (at 6910 and 6930 cm-1, respectively) led to selective generation of two additional conformers of high-energy, ITc and ITa, respectively, which were also observed experimentally for the first time. In addition, these experiments also provided the key information for the detailed vibrational characterization of the 3 conformers initially present in the matrices. On the other hand, UV irradiation (λ = 255 nm) of PG isolated in a xenon matrix revealed that PG undergoes facile photofragmentation through two photochemical pathways that are favored for different initial conformations of the reactant: (a) decarboxylation, leading to CO2 plus benzylamine (the dominant photofragmentation channel in PG cis-COOH conformers ICa and ICc) and (b) decarbonylation, with generation of CO plus benzonitrile, H2O and H2 (prevalent in the case of the trans-COOH conformer, IITa).